If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+2(x+2)=2(x+14
We move all terms to the left:
4x+2(x+2)-(2(x+14)=0
We multiply parentheses
4x+2x-(2(x+14)+4=0
We add all the numbers together, and all the variables
6x-(2(x+14)+4=0
| -3(2x+1)=5(5-4x) | | 2/3y+1/2y=7 | | 2x-43=25 | | X^3-4x=5760 | | 3(13/2a)=-3+a | | n/14=0.1 | | -4t-5=-6t-17 | | n/72=2.4 | | n/10=13.6 | | 9(2x-9.2)=-16.5+8x | | n/5=1.5 | | 3x-3+2(2x+4)=-2(x+5) | | 5.4+v/7=-12.1 | | 2×-7=3x+4 | | 4z/9-8=7 | | 1/3s+14=13 | | x+3/4=1/5 | | 8+9m=4m-7 | | 9y=128 | | 9x-5=2(6x-13) | | 8p+7=87 | | -20=-8v+4(v-6) | | 5k+13=12 | | 4u–16=-56 | | 15x+2=4x+24 | | y+3/8=-6 | | 2x+15+2x+2+6x-7=180 | | -7/3+1/5u=5/2 | | 6z=-75 | | 15x+2x=8x-9 | | 4y+3y-11=52 | | x^2+18x+50=-7 |